COMMUNICATION SKILLS FOR MENTORS IN SOCIAL BUSINESS - Marzano, Gilberto; Zorzi, Simone (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The word mentor comes from “Mentor”, the old man to whom Odysseus entrusted his house and son Telemachus. Accordingly, mentoring can be assumed as the guidance whereby one person shares their experience and expertise to support other people to progress in their own lives and careers.Mentoring encompasses supportive relationships finalized to job performance, leadership practices, a career as well as teaching learning-processes. This paper analyzes the function of mentors in social business and the communication skills they need in using digital media. This paper aims to give an overview of the various aspects and issues related to social mentoring, focusing on the use of digital communication technologies to assist mentors in providing guidance, knowledge, and support. It reports and discusses the preliminary results of the desk research carried out by the authors within the EU project DICCMEM.